Studi Perkembangan Tanah Pada Suatu Toposekuen di Negeri Assilulu Kecamatan Leihitu Kabupaten Maluku Tengah - Ely, Sitna S; Haumahu, Johannis P; Ufie, Condradus (Jurnal Agrosilvopasture-Tech, 2023)
his study aims to identify the morphological and developmental characteristics of the soil and classify the soil type in a toposequence in Negeri Assilulu, Central Maluku Regency. This research used a survey method with transect observation distances and profile observation types. The results showed that there were differences in color characteristics both between layers and between profiles. The three profiles have a distribution of texture classes from loam to dusty clay. The structure of the soil is rounded cuboid, fine-medium in size, and the level of development is weak to moderate. The consistency of the soil is slightly sticky to sticky, has ABwC genetic horizon. Soil type categories in the three soil profiles are Cambisol, including developing soil.